Emperor´s Insolvency and the Economic causes of Beginning of the "Bohemian War" in 1618 - Vorel, Petr (My University, 2021)
The author has formulated a hypothesis that significantly changes the interpretation of the causes of the conflict in Bohemia in 1618. According to him, the decisive impulse was the uncontrollable indebtedness of the monarchy, which resulted in a sovereign default (1615). The Bohemian Diet refused to guarantee the government bonds which resulted in the loss of their value. Between 1615 and 1618, along with the fight for the preservation of religious freedom, a strenuous fight for fiscal reform and control of economic resources was underway. According to this new interpretation, the period between 1615 and 1623 represents a coherent unit of the economic history of the Kingdom of Bohemia: From a sovereign default in 1615, to an armed conflict (1618–1620) galvanized by the financial crisis, to the era right after the defeat of the estates (1621–1623), when the victorious Habsburgs radically interfered in the economic structure of the defeated country. The idea of an extensive economic exploitation of the Kingdom of Bohemia was implemented much sooner than the subsequent forced re-Catholicization.
Zadlužení panovníka a ekonomické příčiny zahájení "české války" v roce 1618
Keywords: Kingdom of Bohemia; Sovereign Default; 1615; Economic Resources; Financial Crisis; Bohemian War; 1618; 1623; království české; vládní bankrot; 1615; ekobomické zdroje; finanční krize; česká válka; 1618; 1623